KCa3.1—a microglial target ready for drug repurposing?. Issue 10 (28th April 2016) - Dale, Elena; Staal, Roland G. W.; Eder, Claudia; Möller, Thomas
Abstract : Over the past decade, glial cells have attracted attention for harboring unexploited targets for drug discovery. Several glial targets have attracted de novo drug discovery programs, as highlighted in this GLIA Special Issue. Drug repurposing, which has the objective of utilizing existing drugs as well as abandoned, failed, or not yet pursued clinical development candidates for new indications, might provide a faster opportunity to bring drugs for glial targets to patients with unmet needs. Here, we review the potential of the intermediate‐conductance calcium‐activated potassium channels KCa 3.1 as the target for such a repurposing effort. We discuss the data on KCa 3.1 expression on microglia in vitro and in vivo and review the relevant literature on the two KCa 3.1 inhibitors TRAM‐34 and Senicapoc. Finally, we provide an outlook of what it might take to harness the potential of KCa 3.1 as a bona fide microglial drug target. GLIA 2016;64:1733–1741 Main Points: Drug repurposing for glial cells might accelerate path to patients. KCa3.1 might be microglia target with an opportunity to repurpose a safe and efficacious drug. The NIH NCATS Institute provides opportunities to partner academia with industry for drug repurposing.